Uptake of influenza vaccination and risk reduction behaviour for respiratory infections: a survey of optometrists in New Zealand. (9th June 2014) - Vosseler, Albert; Wilson, Graham A; Wilson, Nick
<x xml:space="preserve">Abstract</x> Background The aim was to determine the uptake of seasonal influenza vaccination and risk reduction behaviours among a health professional group with close patient contact, namely, optometrists. This group can have close facial proximity to patients during eye examinations. Methods National telephone survey of optometrists in New Zealand. Results Seventy per cent of registered optometrists participated (n = 450 responses). Less than one‐third (29.7 per cent, 95% CI: 27.4 to 32.0) of optometrists reported having had the seasonal influenza vaccination in 2012. The major reason given for not being vaccinated was that the vaccination was considered unnecessary (47 per cent) followed by 'time constraints' (28 per cent). During their last respiratory illness, 82 per cent reported working with symptoms and only 16 per cent reported the use of a face mask. Conclusion There is major scope for increasing uptake of influenza vaccination and other protective behaviour for such health professional groups, especially those characterised by relatively close patient contact. Possible options include educational campaigns and government‐funded vaccinators visiting the workplaces of all health‐care workers.